Analysis of Lens Thickness Distribution Based on Swept-Source Optical Coherence Tomography (SS-OCT). (30th December 2021) - Feng, Xi; Wang, Yong; Liang, Jianheng; Xu, Yali; Ortega-Usobiaga, Julio; Cao, Danmin
Abstract : Objective . This study aimed to analyze the distribution of lens thickness (LT) and its associations in age-related cataract patients based on swept-source optical coherence tomography (SS-OCT). Methods . This cross-sectional study included 59, 726 Chinese age-related cataract patients. Only right-eye data were included in the study. Repeated measures of ocular parameters were performed using an IOL Master 700 device. The distributions of ocular biometric data including anterior chamber depth (ACD), LT, axial length (AL), central corneal thickness (CCT), white-to-white (WTW), and mean keratometry (MK) and their associations with age were assessed. The anterior segment (AS) was measured as the sum of CCT, ACD, and LT, while the vitreous chamber depth (VCD) was calculated as the difference between AL and AS. The values of LT : AL, AS : AL, and VCD : AL in different AL groups and their changes are the main outcome measures used to observe the proportion of the anterior and posterior segments of the eye. Results . Biometric data were available for 59, 726 individuals. The mean age was 68.81 years (range = 40–100); 40.62% were male and 59.38% were female. Mean anterior chamber depth (ACD) was 3.02 ± 0.44 mm, mean LT was 4.51 ± 0.44 mm, mean axial length (AL) was 23.89 ± 1.92 mm, mean central corneal thickness (CCT) was 0.53 ± 0.03 mm, mean white-to-white (WTW) was 11.64 ± 0.44 mm, and mean keratometry (MK) was 44.27 ± 1.65 diopter. Female patients had shorter AL, shallower ACD, smaller CCT and WTW, decreased LT, and steeper corneas (p  < 0.005). ACD revealed the strongest negative correlation (p  ≤ 0.001, r  = –0.682) with LT. Age (p  ≤ 0.001, r  = 0.348) showed a moderate positive correlation, whereas MK (p  ＜ 0.05, r  = 0.011), CCT (p  ≤ 0.001, r  = 0.041) had a weak positive correlation and WTW (p  ≤ 0.001, r  = –0.034) had a weak negative correlation with LT. A nonlinear correlation was found between LT and AL. LT increased with age in both males and females. LT changed variably in eyes with AL less than 27 mm, LT decreased as AL increased, then LT gradually increased as AL increased in extremely long and extra-long eyes (p  ≤ 0.001). LT : AL and AS : AL decreased as AL increased, VCD : AL gradually increased as AL increased in highly myopic eyes, and VCD : AL increased by about 0.01 for every 1 mm increase in AL. Conclusions . Among Chinese age-related cataract patients, we found LT to have the strongest relation with ACD. The lens was thicker in elderly patients and women. The correlation between LT and AL is not a simple negative correlation; with the increase of age, LT decreases first and then increases. The proportion of VCD is constantly rising with the elongation of AL.